Implementation of Differentiated Learning in Science Learning to Improve Learning Activities and Learning Outcomes in Elementary School Students - Firda, Rahmania; Erdiana, Mila; Rahmasari, Novianti Tri (JURNAL PENDIDIKAN DASAR NUSANTARA, 2026)
This study aims to improve student activity and learning outcomes in Static Electricity material. The differentiated learning strategy used is to link the characteristics of learning styles consisting of visual, auditory and kinesthetic in group formation and assignment giving. The method used in this study is classroom action research consisting of cycle I and cycle II. This study was conducted in SDN 253 Gresik class VI with 20 students. Student activity data was measured using an observation sheet consisting of six aspects of activities whose values ​​and learning outcomes were measured using a written test. The results of the study using differentiated learning strategies in cycle I showed an average percentage of learning activities of 78% and an average value of learning outcomes of 70.75 where there were 9 students who completed and 11 students did not complete, while learning in cycle II showed an average percentage of learning activities of 90.83% and an average value of learning outcomes of 93.75 where there were 2 students who did not complete and 18 students completed. Based on the results of the analysis data, it shows that the implementation of differentiated learning on the material Static electricity can increase the activity and learning outcomes of class VI students at SDN 253 Gresik.